The Mediating Role of Trust in Management on Job Satisfaction and Organizational Commitment - Ghimire, Binod (Pravaha, 2020)
Purpose- The paper aims to empirically testing the mediating effect of trust in management in the relationship between organizational justice and personal outcomes. The main purpose of this study is to understand mediating role of trusting the management on organizational justice and its impact on job satisfaction and organizational commitment. Approach- The study is based on the effect of organizational justice, trust in management, job satisfaction and organizational commitment among nursing staff working at different hospitals at Kathmandu Valley. This study incorporates design and distribution of questionnaire to 160 nurses belonging to different hospitals working on different scale of pay level. Findings- Organizational justice alone does not significantly increase job satisfaction as well as commitment in the organization. Trust in management mediates the relationship organizational justice and personal outcome. Organizational justice positively affect personal outcome when mediated by high trust in management. Practical implication- This paper is useful to academicians and organizations to understand the impact of trust in management on the work performance. This study provides practical implications towards nurses and management of hospitals. Management requires change in behavior to develop trusting environment in workplace.